Training, Mobility, and Wages: Specific Versus General Human Capital - Alfred Garloff; Anja Kuckulenz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper considers training, mobility decisions and wages together to test for the specificity of human capital contained in continuing training courses. We empirically analyse the relationship between training, mobility and wages in two ways. First, we examine the correlation between training and mobility. In a second step, we consider wage effects of mobility taking training participation into account. First, we find that training participation is negatively correlated with the mobility decision and that training participation decreases the probability of individuals to change the job. Second, we find that wages are lower for job changers for the group of training participants, so wages decrease when trained individuals are mobile. Finally, training participation negatively affects the individuals's subjective valuation of the quality of their last job change. Taken together, these results suggest that there is some specific human capital, which is incorporated into training and lost when moving between jobs.
Keywords: J41; J62; J31; 330; training; mobility; wages; search; job matching; Weiterbildung; Bildungsinvestition; Arbeitsmobilität; Lohn; Schätzung; Deutschland